O ESPELHO DA JUSTIÇA E O TEATRO DA JURISPRUDÊNCIA (1830 – 1831) - Bacellar, Anna Luiza Sartorio (2022)
The Mirror of Justice is an information vehicle that circulated in Rio de Janeiro in the 19th century, in the exact time span that comprised the last months of the First Reign and the beginning of the Regency. In the scenario of political effervescence and intense transformation, both institutional and legislative, it launched itself as a spokesperson in the difficult pedagogical and civilizing task of revealing problems in the legal environment and undertaking the presentation of resolving proposals. Practically forgotten by historiography, the journal is now rescued as the object and primary source of this research, and submitted to the methods of interpretation of the Collingwoodian approach, by Quentin Skinner (2005) and Jhon Pocock (2003), which end with presentism and put text in context, without forgetting to add it to Reinhart Koselleck's Theory of Concepts (2006). The language and reflections analyzed reached 49 issues of its editorial line and counted on the use of software developed for content analysis, in a complementary way. From its performance as a laboratory of legal experiences, we sought to extract knowledge of the ideas of the time on various fields of Law and even place it in the starting position of Brazilian legal journalism. Furthermore, the newspaper dimensioned the precarious state of Brazilian “justice”, still pending a proper and cohesive legal system, mainly in the procedural field. For all these reasons, it constituted an important space for criticism of the Brazilian Justice Administration, under the structure of what was called the Theater of Jurisprudence. So far, research has shown that the journal not only set out to influence the process of formation of legal culture, previously sharing expectations in order to participate in State affairs, but also, in fact, showed itself as a potential mechanism capable of mirroring the justice in its expression closer to reality.